Research Analysis of Built Environment as a System: Implementing Research Through Design Methodology - Suberi, Hari Kumar (Frontiers in Built Environment, 2022)
Building is a process technology that enables human wellbeing by engaging multitude of stakeholders. However it is often seen in the literature sources that all stakeholders involved for building process are disintegrated, which seems to be management and orientation problem to address the built environment as sustainable system design for new and retrofit building. Addressing built environment as a system this study extensively explores built environment literature to identify global variable that will define the roughly correct system and by using Vester Sensitivity Model analyzes the future leverage potential and variables interdependency. The in-depth literature review and system analysis indicates global variables Enabling condition and New material are potential system leveraging variables for built environment system transition to sustainable design. However the leveraging variables are influenced by other global variables which can only be negotiated for sustainable development goal actualization for future success.